2018
DOI: 10.1016/j.ajog.2018.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem microfocus computed tomography for early gestation fetuses: a validation study against conventional autopsy

Abstract: Postmortem whole-body fetal microfocus computed tomography gives noninvasive, detailed anatomic examinations that are achieved in minutes at high resolution. Microfocus computed tomography may be preferable to magnetic resonance imaging in early gestation fetuses and may offer an acceptable method of examination after fetal loss for parents who decline invasive autopsy. This will facilitate autopsy and subsequent discussions between medical professionals who are involved in patient care and counselling for fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 66 publications
1
73
1
Order By: Relevance
“…This demographic skew could have affected the diagnostic accuracy of PMMR, particularly of cardiac anomalies . One way to combat this limitation in the future may be to image fetuses using 3T MRI or alternatively with microfocus computed tomography (micro‐CT); however, these facilities were not available to us at the time of the study.…”
Section: Discussionmentioning
confidence: 99%
“…This demographic skew could have affected the diagnostic accuracy of PMMR, particularly of cardiac anomalies . One way to combat this limitation in the future may be to image fetuses using 3T MRI or alternatively with microfocus computed tomography (micro‐CT); however, these facilities were not available to us at the time of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Also, on the lower left side, a micro-CT image is shown without staining and on the lower right side a micro-CT image of the same fetus with staining, illustrating the increase of soft-tissue visualization due to staining prolonged staining period of several months in higher concentration (5.5%) did lead to extensive tissue shrinkage, but did not result in better staining of internal structures. Hutchinson et al [17] conclude that 3.75% Lugol for 72 h provides excellent results even for larger specimens (up to 21 weeks of gestation). However, this conclusion is not supported by the supplementary data that accompanied their paper, as a video still of a 15-week-old fetus, stained with 3.75% Lugol for 72 h (Fig.…”
Section: Stainingmentioning
confidence: 99%
“…As the technology advances and scanners become increasingly accessible [16], there is a growing interest in the use of these techniques by radiologists in particular to study fetal anatomy postmortem for different purposes, especially in the field of (forensic) radiology and pathology. In these disciplines, a detailed scan of the fetus can contribute to the assessment of fetal conditions and perhaps eventually may serve as substitute for autopsy to determine the cause of death or to study congenital anomalies [14,17]. However, the collective result of previous studies on the novel applications of these techniques is a complex landscape of highly varied approaches that differ in specimen preparation, staining protocols, CT/MRI hardware, and imaging parameters.…”
Section: Introductionmentioning
confidence: 99%
“…This has the added benefit of allowing non‐destructive assessment, with digital storage and manipulation of the information acquired. Recently published work by Hutchinson et al has shown that fetal micro‐CT for early gestation pregnancy loss has a sensitivity rate of 93.8% when compared with conventional autopsy and may provide an alternative option for post‐mortem examination . It is potentially helpful when a primary diagnosis or verification of a suspected developmental anomaly is required and can offer information that would be missed if performing autopsy alone, eg, for cardiac anomalies …”
Section: Internal and External Morphological Appearances Expected At mentioning
confidence: 99%
“…Nevertheless, this was later discounted, as during normal developmental stages, it is usual for long bones to lengthen over several few days subsequent to Carnegie stage 21. Although maceration is known to be detrimental to micro‐CT analysis of early gestational embryos, in this case, our tissue was obtained fresh, and there was no maceration on imaging or visual examination.…”
Section: Internal and External Morphological Appearances Expected At mentioning
confidence: 99%